Information - information standpoint - informatics - Sokolov, Arkadij (Information & Media, 1994)
Aim of the article is to explain the main connections between the above-mentioned notions and to base further methodological investigation. The article contains four parts: 1. Information: phenomenon? function? fiction?; 2. Unity of information and information viewpoint; 3. Informatics as informative infrastructure and a branch of science; 4. Information as informative viewpoint in the aspects of reflection and organization.The conclusions are drawn that information is the basic notion of the informative viewpoint. Contents and extent of the notion informative viewpoint depends on the subjects of reflection and organization. Information is the informative viewpoint of the investigation in reflection and organization.
Keywords: -